PENGATURAN ARAH AZIMUTH DAN SUDUT TILT PANEL PHOTOVOLTAIC UNTUK OPTIMALISASI RADIASI MATAHARI, STUDI KASUS: BANDUNG – JAWA BARAT - Darussalam, Rudi; Rajani, Ahmad; Kusnadi, Kusnadi; Atmaja, Tinton Dwi (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
This paper discusses about the setup of photovoltaic panel direction (azimuth angle) and angle inclination (tilt angle) which aim to optimize the total solar radiation on tilted surface photovoltaic panel. Setting of azimuth angle and tilt angle in accordance with characteristic location of installation can produce optimum electrical energy. Setting of tilt angle panel varied on 5, 10, 15, 20, 25 and 30° and setting of azimuth angle varied on facing north and facing south using solar radiation data from NASA Surface Meteorology and Solar Energy. This research was conducted in Ciparay, Kabupaten Bandung which is field laboratory hybrid power generation from renewable energy sources. The results of this study found that the optimal tilt angle and azimuth angle are varied between 5 - 10° during October - February with panel facing the south and between 5 - 25° during March – September with panel facing the north. For fixed panel photovoltaic type, the optimal tilt angle is 10° with panel facing to the north. Keywords: photovoltaic, tilt angle, azimuth angle, energy, solar radiation, renewable energy, fixel panel photovoltaic.